Alauddin Al-Samarqandi’s Comprehensive Approach To The Concepts Of «Tafsir» And «Ta’wil» In Islamic Hermeneutics (The Journal of Interdisciplinary Human Studies, 2026)
Alauddin al-Samarqandi was a preeminent Hanafi scholar of Transoxiana during the Karakhanid era, recognized for his profound contributions to Islamic jurisprudence (Usul al-Fiqh) and theology (Kalam). This article delves into al-Samarqandi’s systematic methodological approach to Quranic hermeneutics, specifically his rigorous conceptual distinction between Tafsir (exegesis) and Ta’wil (interpretation). By examining his works, the article explores how al-Samarqandi resolved the epistemological tension between the necessity of rational deduction (ra’y) in jurisprudence and the Prophetic traditions that seemingly condemn interpreting the Quran through personal opinion. His framework not only preserved the orthodox Maturidi tradition but also provided a lasting criterion for distinguishing valid scholarly interpretation from heretical distortion.
Keywords: tafsir; ta’wil; Islamic hermeneutics; Alauddin al-Samarqandi; Hanafi school; Maturidi tradition; Quranic interpretation; ra’y; Transoxiana; Samarkand school